How Delegation Improves Commitment - Grischa Perino (University of Heidelberg, Department of Economics, 2008)
We often use delegation as a commitment device if a government faces problems of timeinconsistency. McCallum (1995, AER P&P) challenged this practice, claiming that delegation merely relocates the commitment problem but does not solve it. In a model where delegation and specific policies are subject to the same commitment technology it is shown that McCallum's conjecture holds if optimal ex-ante policies are fixed. However, with a flexibility-credibility trade-off delegation is both desirable and improves credibility. While delegation does not increase commitment per se it makes it more attractive and increases investments in credibility. Delegation can therefore serve as a valid commitment device.
Keywords: D02; D23; D73; H11; 330; Time-inconsistency; commitment; delegation; Zeitkonsistenz; Glaubwürdigkeit; Neue politische Ökonomie